Translating potential biomarker candidates for schizophrenia and depression to animal models of psychiatric disorders. (September 2011) - Kluge, Wolfgang; Alsaif, Murtada; Guest, Paul C; Schwarz, Emanuel; Bahn, Sabine
Schizophrenia and major depressive disorder are severe mental illnesses, which are diagnosed based on patient interviews. Despite many years of extensive research, scientists have not yet fully deciphered how genetic and environmental factors interact to cause these illnesses. Biomarker tests that can confirm diagnoses of schizophrenia or depression are only now beginning to emerge, and could result in a paradigm shift in this field. These tests will help to evaluate the validity of animal models of psychiatric disorders, which are currently characterized based on behavioral measures. In this article, we explore the utility of translating both behavioral and molecular phenotypes of such models to the corresponding human disorders. This approach may help to provide construct validity to animal models and could lead to the identification of models corresponding to defined subtypes of neuropsychiatric disorders based on molecular profiles. Here, we review the molecular and biological pathway alterations that have been found in animal models of schizophrenia and depression and focus on those that are mirrored by similar abnormalities in human patients. Such parallels may provide insight into the validity of specific animal models and therefore help to provide more valuable and accurate tools for the discovery and development of improved psychiatric medications.